SOSIALISASI SIA PELAPORAN AKUNTANSI UMKM MAGANG MAHASISWA MBKM UNIVERSITAS INDO GLOBAL MANDIRI - Aberta, Fina; Hertati, Lesi; Terrtiavini, Terrtiavini; Heryati, Agustina; Cahyani, Nani; Puspitawati, Lilis (Transpublika Publisher, 2024)
This socialization aims to compare traditional accounting information systems with the latest technology-based accounting information systems in the development of professional quality in the company. In conducting research and analysis, it was found that the latest technology-based accounting information system has advantages in improving the efficiency, accuracy, and availability of financial information. Technologies such as cloud computing, big data, and artificial intelligence allow the process of recording, processing, and reporting financial information to be faster and more accurate. However, the implementation of the latest technology-based systems also faces challenges, such as higher costs and the need for higher technical skills. Changes in culture and work processes are also required to adopt these new technologies. In terms of professional quality development, the use of advanced technology-based accounting information systems can help improve professionals' ability to manage financial information effectively. With access to more accurate and relevant information, accounting professionals can make better decisions and provide greater added value to the company.